Theoretical Kinetics Study of The HO2 and C2H5OH: Hydrogen Abstraction Reaction - Nghia, Nguyen Trong (VNU Journal of Science: Mathematics - Physics, 2020)
C 2 H 5 OH has been using as an alternative fuel for decades; HO 2 also plays a pivotal role in the combustion. The kinetics and mechanism for the reaction between C 2 H 5 OH and HO 2 radical have been investigated using the molecular parameters for the reactants, transition states and products predicted at the CCSD(T)//B3LYP/6-311++G(3df,2p) level of theory. There are ten pair products have been found including C 2 H 5 O + H 2 O 2 (PR1), CH 3 CHOH + H 2 O 2 (PR2), CH 2 CH 2 OH + H 2 O 2 (PR3), CH 3 CH 2 OOOH + H (PR4), C 2 H 5 + HOOOH (PR5), CH 3 CH 2 OOH + OH (PR6), CH 3 CH(OH)OOH + H (PR7), HOCH 2 CH 2 OH + H (PR8), HOOCH 3 + CH 2 OH (PR9), and CH 3 + HOOCH 2 OH (PR10) in which the second and third ones are the major channels. The rate constants and branching ratios for all H-abstraction reactions have been calculated using the conventional transition state theory with asymmetric Eckart tunneling corrections for the temperature ranging from 298 to 2000 K.